Customer behavior in developing customer retention at Seri Malaysia Hotel Johor Bahru / Nur Nadiah Mohd Abbas - Mohd Abbas, Nur Nadiah (Faculty of Business and Management, 2010)
It is important for the company in retaining the customer to have the service at their company. Customer retention is important in evaluating the performances of the services provided. This study will reveal on how customer behavior will influence customer retention towards the company. The objective of the study is to know the level of customer retention at Seri Malaysia Hotel Johor Bahru, to determine the most influence factors that will affect customer retention, to identify the relationship between customer behavior and customer retention at Seri Malaysia Hotel Johor Bahru, to identify correlations between customer behavior and customer retention and to identify the recommendations to attract customer retention at Seri Malaysia Hotel Johor Bahru. The results of the research were obtained by using six methods which was reliability test, frequency distribution, correlation analysis, hypothesis testing, chi-square and backward regression. The process of analyzing and interpreting of the data was presented through tables and all objectives are well defined.